Assessment of factors affecting conception rate in cross bred cows following artificial insemination under field conditions - SINGH, NARINDER; NANDA, A S; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2023)
Studies were conducted to identify the factors affecting fertility in cross bred cows followingartificial insemination (Al) under field conditions. A field survey was carried out on 446 crossbred cows of89 farmers inseminated by 34 AI technicians. The data was analyzed by Artificial Insemination DatabaseApplication (AIDA) a software provided by F AO/IAEA Vienna, Austria. The I•• service conception rate(FSCR) and the overall conception rate (OCR) were 29.4% and 38%, respectively. The OCR was better(48.8%) in cows inseminated 18-23 hours after the onset of estrus. Inseminations done by professionaldegree holders yielded better conception rate (48.7%) as compared to those done by diploma holders(20.4%) or by progressive dairy farmers (30.2%). The OCR was significantly (P
Keywords: Artificial insemination; AIDA; Cross bred cows; Conception rate